If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(3x-1)=60
We move all terms to the left:
-6(3x-1)-(60)=0
We multiply parentheses
-18x+6-60=0
We add all the numbers together, and all the variables
-18x-54=0
We move all terms containing x to the left, all other terms to the right
-18x=54
x=54/-18
x=-3
| 1x/3+2=9 | | -(7w+6)=5(12-w) | | 5m+1≤=4 | | x-24=90.5 | | −4.2x=21 | | 10(q+1)=50 | | 7x+1=5x-9+2x | | y/9+5=15 | | 7(x-3)+1=29 | | -2(-x+3)=4 | | 2(x+0.7=6(x-0.8 | | 10x^2-x-20=0 | | -12r+5=149 | | -6+8=10x-20 | | 7x-77+8x=-2 | | k/6+48=56 | | 4x | | 7(y+2)=77 | | y=3-5y | | 3+8p=35 | | 6c-3=-9 | | -12x+68+16x=32 | | -2=z+57/7 | | 4.5s-12.6=34.6 | | 3x-5=12-15 | | 17=1/3(-9p+6) | | 3x5=x-11 | | p/10-4=1 | | 2/3z=44/1 | | 14.6r+5.7=-78.9 | | -5r-6=29 | | 70-4x+12x=-90 |